Co2 Storage Capacity Estimation Of Depleted Oil And Gas Reservoirs In Indonesia - Utomo P Iskandar; Usman Usman (Scientific Contributions Oil and Gas, 2011)
Implementation of co2 capture and geological storage technology at the scale needed To achieve a significant and meaningful reduction in co2 emissions requires knowledge of The available co2 storage capacity. Various geological formations located across many Islands in indonesia appear to be potential to store the anthropogenic co2, particularly in Depleted oil and gas reservoir. These depleted oil and gas reservoirs are appropriate Candidates for co2 storage. However, the capacity of this geological formation has not Been estimated yet. The objective of this study is to estimate the storage capacity of depleted Oil and gas reservoirs in indonesia using the methodology, developed by carbon Sequestration leadership forum (cslf). Screening result from our databases showed there Were 103 depleted oil and gas fields were considered depleted from their np/ult ratio (hydrocarbon cumulative production over ultimate recovery) which were > 55%. However, Only 48 fields had complete data to estimate. We used the methodology that was Initially developed by cslf but then it had been simplified by poulsen et al. We considered This methodology as the most convenient to use in this country scale of assessment despite Of any simplification had been made. Estimation result showed riau and south sumatra Region have large storage capacities which are around 229 and 144 mtco2 respectively. The estimates of co2 storage capacity reflects the actual capacity that was based on data Availability during the assessment. The potential storage capacity might change as data Becoming more available. Hence, the storage capacity map resulted from this study is not Conclusive estimation. However, this study indicates that indonesia has huge potential of Co2 storage in depleted oil and gas reservoirs.